Humain Capital In Algeria And Its Impact On Economic Growth - Gribi, Nassireddine (University of Eloued جامعة الوادي, 2025)
The study aims to study the impact of human capital on economic growth in Algeria. Through the statistical results, it is clear to us that there is a positive impact of investment in human capital in Algeria on economic growth. As the increase of human capital by one unit will lead to an increase in the economic growth index by 2.36 at the significant level 5%, this reflects the role that human capital plays on economic growth by enhancing the productivity of enterprises within the country, which requires Algeria to work on developing human capital, especially at the qualitative level, by adopting more reforms by improving education, linking it to the labor market, and raising the return on it. Until we reach sustainable economic growth.
Humain Capital In Algeria And Its Impact On Economic Growth: Standard Study During The Period (2000-2022)
مقال
Keywords: Education; Economic Growth; Human Capital; Labor Market; Algeria